HUBUNGAN SUMBER INFORMASI DENGAN TINGKAT PENGETAHUAN REMAJA TENTANG BAHAYA SEKS BEBAS PADA REMAJA DI LUWU TIMUR - Hamalding, Hermawati (Pascasarjana Universitas Negeri Makassar, 2023)
Casual sex has negative impacts on teenagers including psychological impacts, physiological impacts, social impacts and physical impacts. Psychological impacts include feelings of anger, fear, guilt and guilt. Physiological impact of unwanted pregnancy and abortion. The social impact of dropping out of school on students who become pregnant out of wedlock and are excluded from their peers (Arya, 2019). This research aims to determine the relationship between sources of information and the level of knowledge of teenagers about the dangers of casual sex in Class XI students at SMAN 8 East Luwu in 2023. The research design used cross sectional. The research subjects were all 140 teenagers from SMAN 8 East Luwu. Based on the results of the chi-square statistical test using the Statistical Program for Social Science (SPSS) application, the relationship between sources of information and teenagers' knowledge about the dangers of free sex obtained a p value = 0.009 < α=0.05, which means that there is a relationship between sources of information and teenagers' knowledge about the dangers of casual sex. The suggestions in this research are for future researchers to develop other variables that influence knowledge about the impact of casual sex. There is a need to increase socialization about good things through education, distribution of leaflets about the impacts of free sex. Educational institutions are expected to add more references about the impact of free sex.